β-endorphin response to aerobic and anaerobic exercises in Wistar male rats (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Physical exercise is strongly associated with the release of β-endorphin. It is assumed that the type and intensity of physical exercise contributes to the release of β-endorphin. This study aimed to compare levels of β-endorphin in brain tissue in response to aerobic and anaerobic physical exercise. METHODS This study was an experimental laboratory study using 35 male Wistar rats divided into one control group and two physical exercise treatment groups: aerobic and anaerobic. Physical exercise was conducted on an animal treadmill running at aspeed of 20 m/min for 30 min of aerobic exercise and 35 m/min with 1-min intervals every 5 min for 20 min for anaerobic exercises. Each aerobic and anaerobic exercise group was furtherly classified into three subgroups (1×/week, 3×/week, and 7×/week). β-endorphin levels were determined using enzyme-linked immunosorbent assay. The data were analyzed using independent t-test and one-way analysis of variance. RESULTS The highest mean of β-endorphin level was found in the weekly exercise (54.45 [1.41] pg/ml) of aerobic exercise group and daily exercise (70.50 [11.67] pg/ml) of anaerobic exercise group. Mean of β-endorphin level in control group was 33.34 (3.54) pg/ml. A significant increased of β-endorphin mean level (p<0.001) was found in all aerobic and anaerobic exercise groups except the aerobic exercise 7×/week group(37.37 [6.30] pg/ml) compared to control. CONCLUSIONS Both aerobic and anaerobic physical exercise conducted for 6 weeks could increase the level of β-endorphin in brain tissue.